2019
DOI: 10.1093/jas/skz123
|View full text |Cite
|
Sign up to set email alerts
|

Sequential feeding with high-fat/low-crude protein diets for two lines of growing-finishing pigs under daily cyclic high ambient temperature conditions1

Abstract: This study was conducted to evaluate the effects of sequential feeding technique in two genetic lines (GL; Line A [cross having a greater proportion of Pietrain] and Line B [cross having a lower proportion of Pietrain]) of growing-finishing pigs reared under daily cyclic high ambient temperature conditions. Seventyeight castrated male pigs (22 ± 2.5 kg BW) were housed in a single group and were allocated to one of the three feeding programs: control (CON, 24 h control diet), high-fat/low-crude protein (HF/LP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Equipment such as electronic feeders provides a promising approach to evaluate pigs feeding behavior responses since it allows recording automatically information on feed intake of individual pigs in a group-housed condition [ 7 ]. In a previous study, we have demonstrated that pigs selected for improved lean tissue accretion (i.e., with a greater proportion of Pietrain genes) had lower growth performance when housed under daily cyclic high ambient temperature conditions [ 8 ]. We hypothesized that in such conditions, pigs prioritize feed intake in the coolest hours of the day and that their feeding behavior is modulated by genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Equipment such as electronic feeders provides a promising approach to evaluate pigs feeding behavior responses since it allows recording automatically information on feed intake of individual pigs in a group-housed condition [ 7 ]. In a previous study, we have demonstrated that pigs selected for improved lean tissue accretion (i.e., with a greater proportion of Pietrain genes) had lower growth performance when housed under daily cyclic high ambient temperature conditions [ 8 ]. We hypothesized that in such conditions, pigs prioritize feed intake in the coolest hours of the day and that their feeding behavior is modulated by genotype.…”
Section: Introductionmentioning
confidence: 99%
“…The loin eye area was significantly decreased in response to high ambient temperature in commercial pigs, whereas it was not affected by ambient temperature in Piau crossbred pigs. Because protein deposition is directly associated with metabolic heat production [ 25 , 26 ], its reduction at high ambient temperatures may be interpreted as a strategy of commercial pigs to attenuate negative effects of heat stress. Because this response was not observed in Piau crossbred pigs, increased thermotolerance of this genotype could be suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that lipid deposition was not affected by ambient temperature could be associated with the increased energetic cost of protein compared to adipose tissue deposition. For instance, although 2 ATP are necessary to deposit lipid, a peptide bond synthesis from amino acids needs at least 5 ATP [ 26 , 27 ]. This suggested that commercial pigs prioritized inhibiting proteogenesis over lipogenesis at high ambient temperatures to thermoregulate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower feed intake in sows under high ambient temperature can be minimized by combining crude protein reduction with essential amino acid supplementation and energy addition (Renaudeau and Noblet, 2001;Renaudeau et al, 2012). Diets with low crude protein and high energy in the hottest hours of the day, and control diet in the coolest hours of the day under high daily cyclic ambient temperatures have been studied (Fraga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%